Faktor yang mempengaruhi neet pada masa pandemi Covid-19 di Indonesia - Yefita Febria, Angi; Ibrahim, Arief; Kamarni, Neng (Jurnal Paradigma Ekonomika, 2022)
In 2030, Indonesia is predicted to reach the peak of the demographic bonus. However, there is a worrying problem, namely youth unemployment, which reaches 1 in 5 youths aged 15-24 years. This study aims to determine the general description and factors that cause a person to become a NEET in Indonesia using the 2020 Sakernas data. The analytical methods used are descriptive statistics and inferential statistics with binary logistic regression models. The results show that with a 99 percent confidence level, the variables that significantly affect a person's status as a NEET are age, gender, disability, marital status, education, and area of residence, while the impact of COVID-19 has no significant effect.